PENGETAHUAN DAN SIKAP TERHADAP GAYA HIDUP PADA PENDERITA DIABETES MELITUS DI PUSKESMAS GE’TENGAN - Lukas Siamben, Adolfina; Wijaya, Suharnita; Indrawati Ledianan Barung, Sri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Increased sugar in the blood because it accumulates in the body due to disruption of hormones that function to lower sugar levels called diabetes mellitus. Knowledge about diabetes mellitus is very important. Perception or congnitiveness is the most important area for determining a person's behavior. Knowledge is essential to stimulate attitudes and stimuli towards action. The purpose of this study is to determine the relationship between knowledge and attitudes towards lifestyle in people with diabetes mellitus at Ge'tengan Tana Toraja Health Center. This type of research is quantitative research using a crossnsectional approach. With the technique of "total sampling" All patients with diabetes mellitus at PuskesmasgGe'tengan, Tana Toraja was used as a research subject with inclusion and exclusion criteria of 35 people. The independent variable is knowledge and attitude and the dependent variable is the lifestyle of people with diabetes mellitus. The data was analyzed using the Chi-Square statistical test with a value of ρ<0.05. The results of the study found that there was a relationship of knowledge of the lifestyle of people with diabetes mellitus with the results ρ = 0.041 and there was no relationship between attitudes towards the lifestyle of people with diabetes mellitus with the results ρ = 0.462. Conclusion there is a relationship of knowledge to the lifestyle of people with diabetes mellitus and there is no relationship of attitude towards the lifestyle of people with diabetes mellitus